Adaptive Spatial Management to Deal with Postflood Inshore Bycatch in a Penaeid Trawl Fishery. (3rd March 2022) - Taylor, Matthew D.; Johnson, Daniel D.
Abstract: Adaptive spatial management provides a way to balance the conservation of bycatch species and the potential economic effects of bycatch‐induced closures on a fishery, but implementation can be both data and resource intensive. We present a survey exploring a novel approach to adaptively manage an intermittent bycatch issue in an inshore trawl fishery where Sciaenidae bycatch species (including juvenile Mulloway Argyrosomus japonicus, a species of conservation concern) co‐occur with large aggregations of a valuable target species (eastern school prawn Metapenaeus macleayi ), following flood‐induced egression from estuarine habitats. Diurnal sampling surveys followed three flood events and targeted permanent inshore closure zones (designed to protect the normally nocturnally harvested eastern king prawn Melicertus plebejus ) and adjacent inshore nonclosure areas. Sciaenidae abundance was mostly <10 fish/ha trawled, but larger catches generally corresponded with larger catches of eastern school prawn, and these relationships appeared to be steeper within nonclosure zones. There were only minor differences in the size structure of eastern school prawn between zones, and patterns were event and location specific. Negligible eastern king prawn were encountered. The results show that temporarily allowing fishers access to permanent trawl closures following floods may support the exploitation of aggregated target species with reduced interaction with bycatch species of concern. The approach presented here is relevant to the consideration of adaptive spatial management in other trawl fisheries.